The Importance of Interaction in Classrooms for the Process of Teaching and Learning English - Ardi, Jonathan (Edelweiss : Journal Of Innovation In Educational Research, 2023)
The impacts of globalisation have had a considerable impact on English instruction, and because English is a language that is used internationally, it should be learned by everyone. The extent to which teachers are able to communicate and interact with their students is a critical component in determining how effective they are as educators. When it comes to activities in the classroom that take a communicative approach or include classroom engagement, classroom contact is absolutely necessary. One of the most important things that can be done to improve the efficiency of instruction is to include classroom discussions. The primary objective of this study is to investigate the significance of interaction within the classroom setting for the purpose of English education and communication. The purpose of this endeavour is to identify a variety of activities that encourage interaction between students. This research makes use of a library research methodology, in which the data is derived solely from books and articles published in academic journals. This approach adds to a better comprehension of the subject matter of the study. After the researcher had collected all of the relevant sources, they documented all of the pertinent findings that were drawn from the materials that were chosen. The relevance of classroom events for students will be determined by the degree to which the teacher and students co-constructed those experiences. Students can benefit from classroom contact in a variety of ways, including the development of their language store, the enhancement of their communication skills, the enhancement of their confidence, and the strengthening of their relationships with other people. In this article, we will discuss seven different types of activities that engage learners in interaction. These activities include question-and-answer sessions, dialogues and role-plays, matching activities, communication strategies, visual aids such as pictures, puzzles, and problems, discussions and decision-making exercises, the write-pair-switch technique, and cooperative learning methods. It is anticipated that the findings of this research will motivate students to engage in more active participation in English exchanges with their classmates.